X-linked hyper IgM syndrome with severe eosinophilia: a case report and review of the literature - He Li; Yang Cao; Jijun Ma; Chongwei Li (BMC, 2022)
Abstract Background Hyper IgM syndromes (HIGMS) are a group of rare primary immunodeficiency disorders. There are limited reports about HIGMS combined with severe eosinophilia. Case presentation In this report, we described a 2-year-old boy with chronic cough and symptoms of hypoxia. Lung computed tomography (CT) scan showed that diffuse ground-glass changes and eosinophils in peripheral blood increased significantly. Subsequent tests revealed a notable decrease in serum IgG and IgA. The lymphocyte subgroup classification was basically normal. Pneumocystis jirovecii were detected from the bronchoalveolar lavage fluid (BALF) of the patient by metagenomic next-generation sequencing (mNGS). After treatments of caspofungin combined with sulfamethoxazole, intravenous immunoglobulin (IVIG) replacement and anti-inflammatory steroid, the clinical symptoms and pulmonary imaging noticeably improved. The absolute eosinophil count (AEC) also returned to normal range. X-linked hyper IgM syndrome was confirmed by gene test. Two months after the diagnosis, the patient underwent allogeneic stem cell transplantation (HSCT) and has recovered well. Conclusions Children with HIGMS are prone to opportunistic infections such as Pneumocystis jirovecii pneumonia (PJP). Diffuse interstitial lung disease and hypoglobulinemia in a young child predict the diagnosis of a primary immunodeficiency (PID). mNGS has obvious advantages for obtaining etiological diagnosis of children with PIDs. Severe eosinophilia is rarely reported in this kind of PIDs. Considering literature review and the corresponding reaction to steroid, we proposed that eosinophilia in HIGMS might be related to infections. Steroid therapy can quickly relieve eosinophilia but is easy to rebound if the reduction is too fast. Once the diagnosis of HIGMS is confirmed, the earlier the HSCT, the better the prognosis.